KARAKTERISTIK AGROEKOLOGI GARUT (Marantha arundinaceae L.) PULAU MADURA - - Hermansyah; Eko Murniyanto; Kaswan Badami (Universitas Trunojoyo Madura, 2009)
This research purpose to learn agroecology, distribution and potential production of arrowroot in Madura island. Research methode is exploration, done in Madura island on December 2008 until May 2009. The observations include measurements agroecology, distribution, characterization of morphology and potential production. Data could be analyzed descriptively and statistical. Results agroecology observation shows that the average Rainfall during last 10 years as a lot as 1202.983 mm/years. The composition of Nitrogen are as a lot as 0.1342%. Arrowroot crop distribution in Madura island of west to east respectively - participated in the south region, central and central until north. The pattern of distribution is group. Based on the morphology characters there are 3 variations. Potential production of arrowroot is average as a lot as 2.65 tons/ha. Relationship potential production of arrowroot agroecology obtained equation Y = 3.7362 + 0.1441 (X1) + 0.888 (X2) (R2 = 0.523%) at α 95%.